2021
DOI: 10.1200/po.21.00238
|View full text |Cite
|
Sign up to set email alerts
|

Pretest Genetic Education Video Versus Genetic Counseling for Men Considering Prostate Cancer Germline Testing: A Patient-Choice Study to Address Urgent Practice Needs

Abstract: PURPOSE Germline testing (GT) for prostate cancer (PCA) is now central to treatment and hereditary cancer assessment. With rising demand for and shortage of genetic counseling (GC), tools to deliver pretest informed consent across practice settings are needed to improve access to GT and precision care. Here, we report on Evaluation and Management for Prostate Oncology, Wellness, and Risk (EMPOWER), a patient-choice study for pretest video-based genetic education (VBGE) versus GC to inform urgent practice needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…Multiple elements need to be discussed and understood by patients to make an informed decision for testing 2 , 7 , 9 , 10 . To facilitate pre-test information delivery, videos are being studied in which patients view a genetics education video to understand the genetic testing process and considerations before pursuing genetic testing 72 . Patient-reported outcomes in a male population undergoing prostate cancer germline testing from one study ( n = 127) revealed that most men (71%) chose a pre-test video compared with genetic counselling (29%) ( P < 0.001), with no negative effect on patient satisfaction, decisional conflict for genetic testing, cancer genetics knowledge or uptake of genetic testing 72 .…”
Section: Genetics Care Deliverymentioning
confidence: 99%
“…Multiple elements need to be discussed and understood by patients to make an informed decision for testing 2 , 7 , 9 , 10 . To facilitate pre-test information delivery, videos are being studied in which patients view a genetics education video to understand the genetic testing process and considerations before pursuing genetic testing 72 . Patient-reported outcomes in a male population undergoing prostate cancer germline testing from one study ( n = 127) revealed that most men (71%) chose a pre-test video compared with genetic counselling (29%) ( P < 0.001), with no negative effect on patient satisfaction, decisional conflict for genetic testing, cancer genetics knowledge or uptake of genetic testing 72 .…”
Section: Genetics Care Deliverymentioning
confidence: 99%
“…17 More recent work specifically in men considering prostate cancer germline testing, with 71% of men opting for pretest video-based genetic education (relative to genetic counseling), with comparable patient-reported outcomes and uptake of germline testing. 18 Pretest video education is being implemented in some settings, for example, Memorial Sloan Kettering-Integrated Mutation Profiling of Actionable Cancer Targets tumor and normal testing program, in which patients who desire germline DNA annotation receive pretest genetic counseling via an IRB-approved video. 19 Bradbury et al 20 completed the Eastern Cooperative Oncology Group-American College of Radiology Imaging Network National Cancer Institute Community Oncology Research Program EAQ152 study, a randomized trial of web-based genetic education versus usual care in patients with advanced cancer undergoing tumor genetic testing, and found that a web-based video intervention increased patient understanding but did not significantly reduce anxiety, depression, or cancer-specific distress.…”
Section: Discussionmentioning
confidence: 99%
“…17 More recent work specifically in men considering prostate cancer germline testing, with 71% of men opting for pretest video-based genetic education (relative to genetic counseling), with comparable patient-reported outcomes and uptake of germline testing. 18 Pretest video education is being implemented in some settings, for example, Memorial Sloan Kettering-Integrated Mutation Profiling of Actionable Cancer Targets tumor and normal testing program, in which patients who desire germline DNA annotation receive pretest genetic counseling via an IRB-approved video. 19 Bradbury et al 20 Although this PDSA effort seeks to address gaps in patient education, there remain other important systematic challenges around widespread implementation of TGT in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with lower educational attainment were more satisfied with the pretest education, suggesting an even more impactful role for this video and brochure in serving populations with lower education and/or health literacy. With the recent increase in use of telemedicine 31 and initial studies suggesting that patients undergoing genetic testing may even prefer video-based education over traditional genetic counseling, 32 this prostate-specific educational video (available in Supplementary Appendix A, https://www.jurology.com) may serve as a valuable clinical tool. Additionally, the majority of participants in this study did not request an in-person genetics consultation after receipt of results.…”
Section: Discussionmentioning
confidence: 99%